The Impact of Ginger on Preventing Postoperative Ileus after Hysterectomy Under the Enhanced Recovery after Surgery Protocol: A randomized controlled trial - Pongsupanimit , Preeyanuntar; Chaikomin, Reawika; Tripatara , Pinpat; Achariyapota, Vuthinun; Viriyapak, Boonlert; Kanpetpanao, Sudarat; Sathapanapitagkit , Natchanon; Ruengkhachorn, Irene (Thai Journal of Obstetrics and Gynaecology, 2025)
Objectives: To investigate the impact of ginger supplementation on postoperative ileus following hysterectomy under the enhanced recovery after surgery protocol. Materials and Methods: A randomized controlled trial with investigator blinding was conducted. The control arm followed the enhanced recovery after surgery pathway exclusively, while the intervention arm received ginger supplementation. The outcomes assessed postoperatively were bowel function, tolerability of oral intake, wound complications, and adverse effects of treatment. Results: One hundred and sixty patients participated, with 80 allocated to each arm. The median duration of the operative procedure was 130 minutes (Interquartile range [IQR], 105 to 165). Within the first 12 hours postoperatively, 41 patients (25.6%) reported the passage of flatus, and 46 patients (28.8%) experienced ileus. All patients resumed a solid diet within 24 hours. When comparing the control arm to the ginger arm, no significant differences emerged with respect to the postoperative ileus time interval (14.7 ± 7.8 vs 13.6 ± 8.4 hours, p = 0.432), time until the first passage of flatus (17.3 ± 8.1 vs 17.1 ± 7.9 hours, p = 0.869), time to start a solid diet (11.7 ± 6.1 vs 11.2 ± 6.6 hours, p = 0.660), and time to well tolerate a solid diet (18.6 [IQR 14.6 to 20.9] vs 17.3 [IQR 6.2 to 20.1] hours, p = 0.596). The length of the hospital stay did not differ significantly. No adverse effects related to ginger or instances of febrile morbidity were observed. Conclusion: Ginger supplementation did not significantly reduce the incidence of postoperative ileus or the recovery of bowel function following hysterectomy under the enhanced recovery after surgery protocol.